THE IMPORTANCE OF PSYCHOLOGICAL CLIMATE’S EFFECTS TOWARD EMPLOYEE PERFORMANCE - Suratman, Andriyastuti (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
The purpose of this study is to determine a relationship model between Psychological Climate (PC) toward performance within job stress and job satisfaction as a mediator. Primary data were obtained by distributing online questionnaires. The population in this research is the teachers of educational institutions in Indonesia. Obtained 161 people with minimum requirements have worked for one year at the institution (purposive sampling). This research uses validity and reliability test, goodness-of-fit model assumption, and hypothesis testing with SEM analysis of Amos 18.0. Based on data analyzed, four of eight hypotheses proposed are have significant influence; 1) PC on job satisfaction, 2) stress on performance, 3) job satisfaction on performance, and 4) there is a role for job satisfaction in mediating the influence of PC on performance. In addition, there are insignificant effects; 1) PC on stress, 2) PC on performance, 3) job stress on job satisfaction, and 4) job stress have no a significant effect as a mediator between PC on performance.